Findings of the community-based rangeland health workers assessment: Consolidated workshop report - Ebro, Abule; Eba, Bedasa; Said, Mohammed; Lya, Golicha; Abdi, Hamse (International Livestock Research Institute, 2024)
This report contains key findings of the assessment of the potential and opportunities of a community-based rangelands health system, that was presented to participants which comprised community members, kebele leaders, experts and development agents from government offices at kebele, district and zone levels, summarizes workshops discussions and catalogues suggestions on implementation modality and next steps that were identified by workshop participants. This report can be used to help facilitate the implementation of the system of community rangeland health workers (CRHWs) at the community level, considering the views expressed by the participants of the workshop.